Long Term Adaptation to Heat Stress: Shifts in the Minimum Mortality Temperature in the Netherlands - Folkerts, Mireille A.; Bröde, Peter; Botzen, W. J. Wouter; Martinius, Mike L.; Gerrett, Nicola; Harmsen, Carel N.; Daanen, Hein A. M. (Frontiers in Physiology, 2020)
It is essentially unknown how humans adapt or will adapt to heat stress caused by climate change over a long-term interval. A possible indicator of adaptation may be the Minimum Mortality Temperature (MMT), which is defined as the mean daily temperature at which the lowest mortality occurs. Another possible indicator may be the heat sensitivity, i.e. the percentage change in mortality per 1°C above the MMT threshold, or heat attributable fraction (AF), i.e. the percentage relative excess mortality above MMT. We estimated MMT and heat sensitivity/AF over a period of 23 years for older adults (> 65 years) in the Netherlands using three commonly used methods. These methods are Segmented Poisson regression (SEG), constrained segmented distributed lag models (CSDL) and distributed-lag non-linear models (DLNM). The mean ambient temperature increased by 0.03°C/yr over the 23 year period. The calculated mean MMT over the 23-year period differed considerably between methods (16.4 ± 1.2°C (SE) (SEG), 18.9 ± 0.5°C (CSDL) and 15.3 ± 0.4°C DLNM). MMT increased during the observed period according to CSDL (0.11 ± 0.05°C/yr) and DLNM (0.15 ± 0.02°C/yr), but not with SEG. The heat sensitivity, however, decreased for the latter method (0.06 %/°C/yr) and did not change for CSDL. Heat AF was calculated for the DLNM method and decreased with 0.07 %/yr. Based on these results we conclude that the susceptibility of humans to heat decreases over time, regardless which method was used, because human adaptation is shown by either an increase in MMT (CSDL and DLNM) or a decrease in heat sensitivity for unchanged MMT (SEG). Future studies should focus on what factors (e.g. physiological, behavioral, technological or infrastructural adaptations) influence human adaptation the most, so it can be promoted through adaptation policies. Furthermore, future studies should keep in mind that the employed method influences the calculated MMT, which hampers comparability between studies.